Development and application of flood impact maps under climate change scenarios: A case study of the Yilan area of Taiwan - Hsiao, Yi-Hua; Chen, Chun-Che; Chao, Yi-Chiung; Li, Hsih-Chi; Ho, Ching-Hsien; Hsu, Chih-Tsung; Yeh, Keh-Chia (Frontiers in Environmental Science, 2022)
To understand the trend of flood disasters in various regions of Taiwan under climate change, this study used the Yilan area as an example and applied estimated typhoon event data of HiRAM under the scenario of RCP8.5. Based on the results, climate hazard and flood impact maps were plotted. Based on the rainfall change rate of the first 30% of the events in the two periods, the climate hazard map was plotted. For the flood impact map, the SOBEK flood model was used to perform flood simulations for the top 30% of the events in terms of the maximum 24-hour cumulative rainfall in the two periods. The distribution of the maximum accumulated flooding depth and the occurrence probability of flooding with different flooding depths in the two periods were calculated, and the flood impact map was plotted. In the climate hazard map, the rainfall change rate increased in most areas in Yilan. In the flood impact map, taking a flooding depth of ≥0.3 m as an example, the overall flooded area in the middle of the century will increase by approximately 1.7 times compared to that in the base period. It can also be seen the probability of different flooding. This study also applies the flood impact map. It can be seen that the affected areas of paddy fields, fish farms and stock farms have changed due to flooding. In this way, attention can be given to areas of different industries affected by flooding in the future, and relevant disaster mitigation and adaptation strategies can be assessed and developed in advance.